Aspek Psikologis Ibu Postpartum: Studi Kasus - Haryati Sahrir; Ni Luh Gede Sri Wahyudianti; Pratiwi Bayuningrum; Sudin Riyadi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: The postpartum period is a complex transition period for mothers, affecting not only the physical but also the psychological aspects. Hormonal changes, new role demands, and lack of social support can trigger psychological disorders such as baby blues, postpartum depression, and anxiety. Objective: This case study aims to describe the psychological aspects of postpartum mothers and the factors that influence them. Methods: This study used a qualitative approach with a case study design. The subject was a mother on day 10 of postpartum who was experiencing emotional distress. Data were collected through in-depth interviews, observations, and a review of medical documentation. Results: The study results showed that the mother experienced symptoms of baby blues, including feelings of sadness, crying easily, fatigue, and excessive anxiety. Factors influencing the mother's psychological condition include hormonal changes, lack of husband's support, physical exhaustion, and a lack of understanding about postpartum adaptation. Conclusion: The psychological aspects of postpartum mothers require special attention from healthcare professionals and families. Early detection and psychosocial support are crucial to prevent more severe psychological disorders.